Strategi Penegakan Hukum Pidana terhadap Pelaku Tambang Batu Hitam Ilegal di Wilayah Suwawa - Hidayat, Irawan; Moonti, Roy Marthen; Ahmad, Ibrahim (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This research examines criminal law enforcement strategies against perpetrators of illegal black stone mining in Suwawa, Gorontalo, with a normative-empirical approach. illegal mining activities in this region not only violate the law, but also damage the environment and create social conflicts. Although there is a strict legal basis, its implementation is still weak due to weak coordination between institutions, the involvement of unscrupulous officials, and the lack of economic alternatives for the community. This research identifies that repressive approaches alone are ineffective, so an integrative strategy is needed that includes restorative justice, strengthening customary law, digitizing surveillance, and empowering the local economy. Structural barriers such as power relations, weak surveillance and social resistance are the main hindering factors. This research recommends institutional reform and community engagement as keys to the success of fair and sustainable law enforcement in addressing environmental crimes such as illegal mining.